Analyzing and Detecting Opinion Spam on a Large-scale Dataset via Temporal and Spatial Patterns - Li, Huayi; Chen, Zhiyuan; Mukherjee, Arjun; Liu, Bing; Shao, Jidong (Proceedings of the International AAAI Conference on Web and Social Media, 2021)
Although opinion spam (or fake review) detection has attracted significant research attention in recent years, the problem is far from solved. One key reason is that there is no large-scale ground truth labeled dataset available for model building. Some review hosting sites such as Yelp.com and Dianping.com have built fake review filtering systems to ensure the quality of their reviews, but their algorithms are trade secrets. Working with Dianping, we present the first large-scale analysis of restaurant reviews filtered by Dianping’s fake review filtering system. Along with the analysis, we also propose some novel temporal and spatial features for supervised opinion spam detection. Our results show that these features significantly outperform existing state-of-art features.